Analisis Kesulitan Peserta Didik Dalam Menyelesaikan Soal Cerita Pada Siswa Kelas VII SMP TRIPLE J - Abdullah Hammuda Ramadhan; Alfiatussyifa Alfiatussyifa; Bayu Aji; Nissa Nur Fadillah (PT. ALHAFI BERKAH INDONESIA, 2023)
Students who have difficulty learning math often make mistakes in counting and solving story problems. One of the common difficulties students experience is when working on story problems because they may not understand the meaning of the problem and may be confused when determining the calculation operation to be used. The subjects in this study were seventh grade students of TRIPLE J Junior High School experiencing difficulties in the process of learning mathematics story problem material. The purpose of the study was to determine the causes of students' difficulties in understanding and solving a story problem. How are efforts to overcome math learning difficulties. Efforts that can be made by teachers to improve a student's ability are able to understand learning methods that are in accordance with the capacity of students, and efforts that can be made by parents are to provide learning facilities and costs while emotional support in the form of advice, advice and appreciation. Most parents provide material support but forget to provide emotional support. Even though both are very important. With emotional support from parents, children will feel appreciated for their hard work in learning.